A Fuzzy Group Decision Making Approach for Agility Evaluation in Aviation Industry - Dursun, Mehtap; Goker, Nazli; Ogunclu, Osman (Lecture notes in engineering and computer science, 2017)
The problem of dealing with unpredictable and uncertainty emerges the agility concept which denotes the capability of firms for responding immediately to environmental changes. To obtain supply chain agility, agile supplier selection becomes a crucial managerial problem due to its multi-objective framework with conflicting criteria. This study introduces a fuzzy group decision making approach for agile supplier evaluation. A case study conducted to determine the most appropriate fuel supplier in aviation industry is introduced to illustrate the application of the decision methodology.